2013
DOI: 10.1016/j.cbpa.2013.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Responses of insulin-like growth factor (IGF)-I and two IGF-binding protein-1 subtypes to fasting and re-feeding, and their relationships with individual growth rates in yearling masu salmon (Oncorhynchus masou)

Abstract: Responses of insulin-like growth factor (IGF)- 12University, 2-9-1 Sakura, Nanae, Kameda-gun, Hokkaido 041-1105, Japan. 32Fasting/re-feeding also affected their mRNA levels in the liver. These results suggest that 33 circulating IGF-I and IGFBP-1b could serve as positive and negative indices of growth, 34respectively, in masu salmon. Different sensitivities of IGBP-1a and IGFBP-1b may be useful to 35assess a broad range of catabolic conditions when they are combined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
42
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 52 publications
(92 reference statements)
13
42
2
1
Order By: Relevance
“…To investigate potential catabolic responses of IGFBPs, we cloned the Atlantic salmon igfbp1a, which has been suggested to limit IGF signaling during starvation in masu salmon (O. masou; Kawaguchi et al, 2013). We found a down-regulation of igfbp1a in muscle of both Atlantic salmon and rainbow trout at elevated temperatures confirming that igfbp1a may be an important metabolic regulator of IGF signaling in muscle of salmonids.…”
Section: Plasma Igf-1 and Igfbp-1bsupporting
confidence: 62%
“…To investigate potential catabolic responses of IGFBPs, we cloned the Atlantic salmon igfbp1a, which has been suggested to limit IGF signaling during starvation in masu salmon (O. masou; Kawaguchi et al, 2013). We found a down-regulation of igfbp1a in muscle of both Atlantic salmon and rainbow trout at elevated temperatures confirming that igfbp1a may be an important metabolic regulator of IGF signaling in muscle of salmonids.…”
Section: Plasma Igf-1 and Igfbp-1bsupporting
confidence: 62%
“…Hepatic IGFBP-1 is believed to indicate catabolic conditions or negative growth in fish species because the expression of hepatic IGFBP-1 increases during fasting. Increased hepatic IGFBP-1 during fasting has been reported in many fish species, including Japanese Amberjack (Pedroso et al 2009b), Atlantic Salmon (Hevrøy et al 2011), Masu Salmon Oncorhynchus masou (Kawaguchi et al 2013), and Channel Catfish (Peterson and Waldbieser 2009). Only the results of lysine supplementation in Atlantic Salmon (Hevrøy et al 2007) are consistent with our finding that increased hepatic IGFBP-1 expression accompanies increased growth.…”
Section: Discussionsupporting
confidence: 93%
“…However, the mean of gh mRNA levels was slightly higher in smaller larvae than in large larvae, this trend conforms to the expectations associated with the poor nutritional status (Wood et al, 2005;Norbeck et al, 2007;Savage, 2013). Conversely, was observed uniformity in igf-1 mRNA levels between the larvae groups, in contrast to the most fasting reports in different fish species (Wood et al, 2005;Norbeck et al, 2007;Peterson & Waldbieser, 2009;Reinecke, 2010;Kawaguchi et al, 2013;Tian et al, 2015;Taniyama et al, 2016). However, Wen-Ying et al (2012) in Carassius auratus gibelio, Breves et al (2014) and Fox et al (2010) in Mozambique tilapia (Oreochromis mossambicus), and Hevrøy et al (2011) in Atlantic salmon (Salmon salar) only observed significant differences at the protein le- Figure 4.…”
Section: Discussioncontrasting
confidence: 53%
“…The igfbp-1 and gck gene expressions are regulated by nutritional status or the glucose levels. The igfbp-1 is regulated by insulin levels and in consequently with glucose levels (Lee et al, 1993) and fasting increase its mRNA levels in fish (Shimizu et al, 2006;Hevrøy et al, 2011;Kawaguchi et al, 2013;Breves et al, 2014), according to the our study results. On the other hand, gck is a liver enzyme that catalyzes the phosphorylation of glucose to glucose-6-phosphate (Enes et al, 2009), is associated with individual nutritional status and showing an upregulation by feed intake (Caseras et al, 2000;González-Alvarez et al, 2009;Panserat et al, 2014).…”
Section: Discussionmentioning
confidence: 53%